Mutant dominant-negative rhodopsin∆I256 causes protein aggregates degraded via ERAD and prevents normal rhodopsin from proper membrane trafficking - Cao, Bowen; Dahlen, Johanna Valentina; Sen, Merve; Beyer, Tina; Leonhard, Tobias; Kilger, Ellen; Arango-Gonzalez, Blanca; Ueffing, Marius (Frontiers in Molecular Biosciences, 2024)
Dominant mutations in the rhodopsin gene (Rho) contribute to 25% of autosomal dominant retinitis pigmentosa (adRP), characterized by photoreceptor loss and progressive blindness. One such mutation, Rho ∆I256 , carries a 3-bp deletion, resulting in the loss of one of two isoleucines at codons 255 and 256. Our investigation, using recombinant expression in HEK293 and COS-7 cells, revealed that Rho ∆I256 , akin to the known adRP mutation Rho P23H, induces the formation of rhodopsin protein (RHO) aggregates at the perinuclear region. Co-expression of Rho ∆I256 or Rho P23H with wild-type Rho WT , mimicking the heterozygous genotype of adRP patients, demonstrated the dominant-negative effect, as all isoforms were retained in perinuclear aggregates, impeding membrane trafficking. In retinal explants from WT mice, mislocalization of labeled adRP isoforms at the outer nuclear layer was observed. Further analysis revealed that RHO ∆I256 aggregates are retained at the endoplasmic reticulum (ER), undergo ER-associated degradation (ERAD), and colocalize with the AAA-ATPase escort chaperone valosin-containing protein (VCP). These aggregates are polyubiquitinated and partially colocalized with the 20S proteasome subunit beta-5 (PSMB5). Pharmacological inhibition of proteasome-or VCP activity increased RHO ∆I256 aggregate size. In summary, RHO ∆I256 exhibits dominant pathogenicity by sequestering normal RHO WT in ER aggregates, preventing its membrane trafficking and following the ERAD degradation.